1994
DOI: 10.1136/hrt.71.6.511
|View full text |Cite
|
Sign up to set email alerts
|

QT interval dispersion: a non-invasive marker of susceptibility to arrhythmia in patients with sustained ventricular arrhythmias?

Abstract: Objective-To assess QT interval dispersion on the surface electrocardiogram in patients with sustained ventricular arrhythmias.Design-A retrospective and prospective blinded controlled study of patients referred for investigation of ventricular arrhythmias at a tertiary cardiac centre. Patients and methods-89 consecutive patients with sustained ventricular arrhythmias due to chronic ischaemic heart disease, cardiomyopathy, or ventricular tachycardia (VT) in a normal heart. 32 patients did not meet the inclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
96
0
4

Year Published

1999
1999
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(104 citation statements)
references
References 21 publications
4
96
0
4
Order By: Relevance
“…At baseline the heart rate was 73 (10) beats per min in 2GLIB and 76 (9) in +GLIB and at T = 150 the heart rates were 77 (14) and 76 (12) in 2GLIB and +GLIB, respectively.…”
Section: Effects Of Hypoglycaemiamentioning
confidence: 98%
“…At baseline the heart rate was 73 (10) beats per min in 2GLIB and 76 (9) in +GLIB and at T = 150 the heart rates were 77 (14) and 76 (12) in 2GLIB and +GLIB, respectively.…”
Section: Effects Of Hypoglycaemiamentioning
confidence: 98%
“…Correction of the QT interval for the heart rate (QTc) was obtained through Bazett's formula (QT/√RR) [8][9][10] . Dispersions of the QT and QTc intervals were calculated, respectively, as the subtraction between the greatest and the smallest QT and QTc intervals in the 12 electrocardiographic leads [11][12][13] .…”
Section: Methodsmentioning
confidence: 99%
“…[3][4][5] QT and QTc dispersion (QTD, QTcD) obtained by using standard 12-lead ECG is a marker of nonhomogeneous ventricular repolarization 6 and is known to be related to severe ventricular arrhythmias. 7 It is reported that QTD increases because of an increase in heterogeneity of ventricular repolarization caused by transient myocardial ischemia occurring as a result of stress. 8,9 On the other hand, it has been shown that QTD decreases subsequent to successful thrombolysis in acute myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%